THE EU WATER FRAMEWORK DIRECTIVE AND ITS IMPLEMENTATION IN THE JURISPRUDENCE OF THE COURT OF JUSTICE OF THE EU - Tubić, Bojan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2016)
This paper deals with the analysis of the creation of the EU Water Framework Directive and its implementation in the jurisprudence of the ECJ. It represents one of the most important acts in the field of environmental protection in the European Union. Its provisions are related to the establishment of the objectives of the environment quality, for surface waters and groundwater, for regulation of disposal of dangerous substances in those waters or for monitoring and sampling of waters. The Directive extends the objectives of environmental protection over the existing legislation of the EU and it includes and extends the criteria for the control of waste disposal and provides a comprehensive framework for control and reporting in this field. The Directive envisages that Member States would provide the establishment of registers of all areas lying within each river basin which have been designated as requiring special protection under specific EU legislation for the protection of their surface water and groundwater or for the conservation of habitats and species directly depending on water. In order to establish a coherent and comprehensive overview of water status, Member States should provide the establishment of programmes for the monitoring of water status within each river basin district. Monitoring is needed in order to establish the efficiency of planes of management of river basins and to help in the process of their periodical revisions. The ECJ, in its judgments, has insisted on implementation of the Directive although not excessively formalistic. Also, its jurisprudence is important for interpretation of certain standards introduced by the Directive.